Synchronization of Multiple Independent Subarray Antennas: An Application for Angle of Arrival Estimation - BniLam, Noori; Steckel, Jan; Weyn, Maarten (IEEE transactions on antennas and propagation, 2019)
In this paper, we present a new algorithm to synchronize multiple individual receiving subarray antennas to form an augmented array antenna system. This augmented array antenna has a large antenna aperture that can be used for angle of arrival (AoA) estimations and it provides a better AoA estimation accuracy than the individual subarray antennas. The proposed algorithm synchronizes the time and the frequency of the different subarray antennas, using a joint maximum likelihood (ML) optimization for a data-aided received signal. The phase coherency between the subarray antennas is achieved by using a combination of the least mean square and ML algorithms. The experimental results and the simulation example show that the proposed algorithm: 1) is stable in estimating the augmented array antenna pattern; 2) provides more accurate AoA estimations than the individual subarray antennas; 3) has no limitation to the structure of the augmented array antenna in space; and 4) converges very fast. Furthermore, the experimental results prove the feasibility of using AoA estimation techniques for Internet of Things localization in outdoor environments.